THE 2008 GEORGIAN CRISIS AND THE LIMITS OF EUROPEAN SECURITY GOVERNANCE - DEMÝRAÐ, Yelda; TANGÖR, Burak (CENTRAL ASIA AND THE CAUCASUS, 2011)
The clashes in the ethnic regions of South Ossetia and Abkhazia are not only about Georgia’s territorial integrity. Moreover, when analyzed from a different perspective, it becomes clear that the ethnic problems in the region are not only an issue between the ethnic groups and the central government. The ethnic problems in Georgia also depend on a change in the perception of the external actors’ interests. This means that when the solution to problems coincided with the interests of the international actors, Georgia was able to solve the problem, as in the case of Ajaria.1 However, when the solution contradicted the interests of the international actors the clashes could not be resolved and the Georgian government was ineffective, as in the cases of South Ossetia and Abkhazia. The clashes determined not only the domestic policy of the Georgian government and the country’s social and economic development, but also Georgia’s foreign policy. Consequently, in order to strengthen its position and maintain its territorial integrity, Georgia shifted to the EU-U.S. axis in order to counterbalance Russia, which supported the ethnic minorities in the region. So it was argued that the democratic breakthrough in Georgia in 2003 happened because the local activists appealed to EU norms and standards and because they received strong support from the EU and its member states.2 Moreover, the EU supported the multilateral efforts to constrain the use of force through arms control and disarmament initiatives and provided financial and technical assistance to projects aimed at combating the accumulation and spread of small arms in Georgia and South Ossetia. The EU set up a rule-of-law operation in Georgia, the EUJUST Themis operation (July 2004), which was not a military mission. Georgia views its relations with the EU as an economic and political partnership that will culminate in EU membership in due course.3In 2004, the EU and NATO expanded into the former Soviet expanse. The Russians regarded NATO membership of the Baltic countries as an encroachment on the country’s traditional periphery. The Russian leadership was alarmed by the West’s active support of the regime change in Georgia. The West was keenly interested in Russia’s own neighborhood. As the primary Western security organization, NATO epitomizes Russia’s insecurities.4The first part of the study describes the theoretical framework of governance and explains the management, coordination, and regulation procedures practiced by the security-related international institutions. The second part discusses the Georgian crisis and its historical background, to provide a better understanding of the crisis, and analyzes the interests of the international actors that triggered the crisis. The third part takes a look at the programs being implemented by international institutions with respect to Georgia. The concluding part evaluates the roles and impact of the international institutions during the crisis.